Susceptibility of Phytoseiulus persimilis and Neoseiulus californicus (Acari: Phytoseiidae) to commonly-used insecticides approved for managing arthropod pests in Florida strawberries - Braden Evans; Karol Krey; Justin Renkema (EDIS, 2018)
The aim of this 9-page document is to inform Florida strawberry producers and Extension personnel on the compatibility of registered miticides and insecticides with commercially available predatory mites used as biological controls. Written by Braden Evans, Karol Krey, and Justin Renkema and published by the UF/IFAS Entomology and Nematology Department, August 2018. http://edis.ifas.ufl.edu/in1216